Teachers' views on the role of context in mathematical literacy - Mthethwa, Themba M. (My University, 2008)
This study focused on teachers’ views on the role of context in Mathematical Literacy. The study falls within a constructivist framework. The research method used was a case study involving two teachers. The data for the study was collected from teachers through semi-structured interviews and was collected from learners through mathematical literacy tasks. In the analysis of the research data, five issues are identified and discussed: They are concerned with (a) the balance between content and context, (b) the relation between context and access to mathematics, (c) links between context and interest, (d) context and language and (e) context as a barrier in mathematics. The study concludes that real life context is very important and useful in teaching and learning mathematics. However, teachers need be careful in selecting context because inappropriate context can become a barrier to learning. The report concludes with recommendations for classroom practice, teacher education and further research.
Keywords: Mathematical literacy; Context; Teaching